Raising expectations (and raising hell): my decade fighting for the labor movement - McAlevey, Jane (London, 2014)
"In 1995, in the first contested election in the history of the AFL-CIO, John Sweeney won the presidency of the nation’s largest labor federation, promising renewal and resurgence. Today, less than 7 percent of American private-sector workers belong to a union, the lowest percentage since the beginning of the twentieth century, and public employee collective bargaining has been dealt devastating blows in Wisconsin and elsewhere. What happened?